VARIABILITY OF GENES OF FOLATE CYCLE IN CHILDREN WITH ESSENTIAL ARTERIAL HYPERTENSION - V. V. Dolgikh; S. E. Bolshakova; E. S. Philippov; M. V. Gomellya (Acta Biomedica Scientifica, 2012)
We realized, the definition, of polymorphic variants of genes of folate cycle (C677T, A1298C, A66G) in children with, essential hypertension, having the burdened, and not burdened, hereditary anamnesis of thrombosis. Frequency of the incidence of low functional allele polymorphisms C677T and. A1298C didn't exceed, ubiquitous in the general population, and. in agreement with, those obtained, in other studies, with, an unfavorable genotype GG A66G gene was more frequent than in the population. In all groups of children studied, most often occurred in the carriage of any one of the polymorphic genes, but the combination, of two or even three adverse alleles also met with, relatively high, frequency. No statistically significant differences in the distribution, of genotypes between groups were found.